DEVELOPMENT OF A SUPPLEMENTARY TECHNIQUE FOR DETERMINING IN SITU STRESS MAGNITUDE USING ACOUSTIC WAVE PROPAGATION - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2006)
In accordance with the increasing awareness of the importance of in situ stress information in the design of various geotechnical and other petroleum related subsurface engineering in Indonesia, a complete knowledge of the insitu stress is a fundamental requirement. Basically, complete information of the insitu state of stress means both the trends and magnitudes of the principal in situ stresses. Some stress determination techniques can provide a complete stress tensor (e.g. differential strain analysis, DSA, method), some provide an incomplete tensor (e.g. sleeve fracturing method), and some provide merely the directions of the principal stresses. The Shear wave (S-wave) splitting technique presented by Widarsono et al (1998), following the earlier works made by Yale and Sprunt (1989), obviously falls in the last category. In some cases, which usually do not require in situ stress information regarding the magnitudes as an input parameter, principal stress directions still provide useful information. Nevertheless, the expanding use of in situ stress information requires, as stated above, a complete information, which means the stress magnitudes as well as directions. Designs of hydraulic fracturing, wellbore stability, and prevention of sand problems are among examples for which information about in situ stresses is required. In relation to the requirement outlined above, the effort which results are presented in this paper was devoted to presenting efforts to predict in situ stress magnitude by using ultrasonic wave propagation. This paper mainly presents efforts to find relations between acoustic propagation and in situ stress magnitude with an ultimate goal to provide the S-wave splitting technique presented in Widarsono et al (1998) with a means for estimating stress magnitudes.